Equity aversion, inequality aversion and economic welfare: On the macroeconomic substantiation of microeconomic utility functions - Friedrich L. Sell; Felix Stratmann (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2009)
In this paper, we first model the dynamics of an economy, making use of a simple, almost trivial circular flow analysis. Then, we demonstrate the effects of "keeping up with the Joneses" as well as of "keeping ahead of the Smiths" in private consumption and the role of innovation and imitation for private investment and economic growth. In either case, we detect both a tendency towards convergence (inequity aversion) and towards divergence (equity aversion) in the macro economy. On the background of the macroeconomic analysis we then turn to a microeconomic view and discuss how the characteristics, functions and findings of selected fairness models which include social preferences change when "equity aversion" is integrated into the theoretical framework. Thereafter, the collected results of both micro and macroeconomic analysis allow us to draw a series of conclusions concerning economic policy in different areas. – – In einem ersten Abschnitt modellieren wir zunächst die Dynamik einer Volkswirtschaft, stark vereinfacht, mithilfe trivialer Kreislaufzusammenhänge. Anschließend demonstrieren wir für Konsum (Nacheifern vs. Abstand halten) und Investition (Innovation vs. Imitation) die Tendenzen zu Konvergenz (Ungleichheitsaversion) und Divergenz (Gleichheitsaversion) in der Makroökonomie. Mit den Ergebnissen der makroökonomischen Analyse wenden wir uns der mikroökonomischen Modellebene zu und zeigen, wie sich die Eigenschaften, Zielfunktionen und Ergebnisse von ausgewählten Fairness-Modellen mit sozialen Präferenzen bei Integration von "Gleichheitsaversion" in den theoretischen Rahmen ändern. Die gesammelten Resultate der makro- und mikroökonomischen Analyse ermöglichen uns dann eine Reihe interessanter wirtschaftspolitischer Schlussfolgerungen, beispielsweise für die Konjunkturpolitik oder die Vertragsgestaltung am Arbeitsmarkt.
Keywords: E21; E22; D63; D01; D92; 330; economic welfare; inequity aversion; fairness concepts; Gerechtigkeit; Soziale Wohlfahrtsfunktion; Konsuminterdependenz; Makroökonomik; Kreislaufanalyse; Konsumentenverhalten; Investition; Theorie